PERBANDINGAN HISTOLOGIS MIDGUT Aedes aegypti AKIBAT TEMEPHOS DAN EKSTRAK Citrus hystrix - Rambung, Etha (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
There has been an increase in dengue cases (in 2022) with a total of 1,135 deaths, of which 73% were children aged 0-14 years, so the government is trying to eradicate dengue with a target of zero deaths by 2024. Temephos is reported to be resistant and another plant that has a larvicidal effect is the leaves of Citrus hystrix DC. This study aims to compare the histological features of the midgut larvae of Ae. aegypti round cut due to the effect of temephos and ethanol extract of C. hystrix leaves. Research method Post test only control group design. Samples of Ae. aegypti third instars were given C. hystrix leaf ethanol extract doses of 80 ppm, 400 ppm, 1500 ppm (LC 50%), distilled water (positive control) and temephos (negative control). At each given dose, there are 3 replications. After that, histopathological preparations were made and the epithelial length was measured (round body cross section). The results of the Mann Whitney test between the 1500 ppm dose group and the temephos group were p = 0.268 > 0.5. So it was concluded that there was no difference in the histological appearance of the midgut of Ae. aegypti round pieces due to the influence of temephos and ethanol extract of C. hystrix leaves at a dose of 1,500 ppm. Methanol extract of C. hystrix leaves causes changes in the histological appearance of the midgut of Ae. aegypti round pieces which increased with increasing concentration of the extract.